Memaknai Cinta Dalam Bingkai Erich Fromm Sebagai Refleksi Pada Fenomena Gray Divorce - Wasty P. Gea; Zai, Albertus; Zai, Julianus; Lalumba, Herliana; Albertus Daniel (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Individualism and consumerist culture are inherent in the contemporary era, self-interest emerges. The meaning of love has been reduced, personal interests have become basic needs, this is fundamentally the root of the Gray Divorce phenomenon. In this research, researchers used qualitative and descriptive methods. Erich Fromm's perspective invites individuals who decide to choose Gray Divorce to turn over a new leaf and share love with others. Get out of the shackles of individualism and give love to those around you. When we give love, we also get love.